ISOLATION, MOLECULAR CHARACTERIZATION, ANTAGONISM AND OPTIMAL PRODUCTION OF SPORES OF Trichoderma Harzianum BY SOLID FERMENTATION APPLYING A BY-PRODUCT OF Oryza sativa (RICE) AS A SUBSTRATE - Oscar Christian Medina Carpio (2021)
Modern agricultural treatment affects soils by reducing their microbial flora and stimulates pathogens to resist the effect of agrochemicals, although there are biological options on the market, these are not competitive, different efforts are made to develop biological controllers that increase the percentage of viable spores, better performance of the substrate design and aggressive antagonism against the pathogen, to carry out these evaluations the present research applied a random factorial design resulting in a matrix of 20 experimental units to determine the concentration values for the design of the substrate and optimal viability spores of Trichoderma spp. by solid fermentation applying a byproduct of Oryza sativa (rice) as substrate.The study strains were molecularly identified as Trichoderma Harzianum sp. and Fusarium oxisporum sp. which were faced in antagonism tests identifying a competitive and inhibitory behavior of Trichoderma Harzianum sp., optimal concentration and percentage of viability values were identified during experimentation, being 3.7925 x 108 CFU / mL and 86.74% respectively resulting from 250 g of rice, with 15 mL of molasses at 15% concentration, 2.5 mL of inoculum and aeration with fine perforations 5 cm high above the substrate and spaced 3 cm between them. The theoretical optimum showed values of 4.13x 108 CFU / mL concentration and 85.15% viability. Finally, the antagonistic action of Trichoderma spp. against Fusarium spp. by dual culture it was 70.3190% on average of the three repetitions carried out.